Nuclear Coupling of (33)S and the Nature of Free Radicals in Irradiated Crystals of Cystine Dihydrochloride: Part II, Charged Radicals - Hadley, Joseph H. (1974)
The (33)S hyperfine structure has been observed in negatively charged cystine molecule-radicals RCH(2)(SS)(-)CH(2)R. The coupling, found to be axially symmetric about the SS bond, proved the orbital of the unpaired electron to be an antibonding SS σ(*) orbital with the spin density shared equally between 3p(σ(*)) orbitals of the two sulfurs. The (33)S hyperfine structure could not be detected for a second radical produced by irradiation of the cystine hydrochloride crystal at 77°K, but interpretation of the proton hyperfine structure and g tensor observed by others led to the conclusion that this radical is the positively charged cystine molecule RCH(2)S(+)SCH(2)R with the spin density concentrated in a 3p orbital of one S and perpendicular to the SS bond.